The effectiveness of transarterial chemoembolization in recurrent hepatocellular-cholangiocarcinoma after resection. - Seong Kyun Na; Gwang Hyeon Choi; Han Chu Lee; Yong Moon Shin; Jihyun An; Danbi Lee; Ju Hyun Shim; Kang Mo Kim; Young-Suk Lim; Young-Hwa Chung; Yung Sang Lee (PLoS ONE)
Background Combined hepatocellular-cholangiocarcinoma (cHCC-CC) can present as a hypervascular or peripherally enhancing tumor in dynamic imaging. We evaluated the effect of transarterial chemoembolization (TACE) on prognosis according to post-operative recurrence imaging patterns. Methods We retrospectively analyzed 42 cHCC-CC and 59 hepatocellular carcinoma (HCC-control) patients at the Asan Medical Center. We classified recurrent cHCC-CC according to enhancement pattern (globally enhancing: GE cHCC-CC, peripherally enhancing: PE cHCC-CC) and evaluated tumor response, time-to-local progression (TTPlocal), and overall survival (OS). Results The GE cHCC-CC group had a significantly higher best objective response rate (complete remission + partial response) than the PE cHCC-CC group (36% vs 0%, P = 0.005), and it was comparable to that of the HCC-control group (35.6%, P = 0.97). TTPlocal in the GE cHCC-CC group was significantly shorter than in the HCC-control group (6.6 vs 27.1 months, P < 0.001), and was not significantly different from that in the PE cHCC-CC group (5.3 months, P = 0.12). OS was 12.4 months, 52.8 months, and 67.5 months in the PE cHCC-CC, GE cHCC-CC, and HCC-control groups, respectively (Ps < 0.05). The adjusted hazard ratios (HRs) for TTPlocal and OS revealed an independent association with enhancement pattern of recurrent cHCC-CC (TTPlocal: HR 2.46; 95% CI 1.10-5.46; P = 0.03; OS: HR 5.97; 95% CI 2.38-14.96; P < 0.001). Conclusions The GE cHCC-CC group showed better response and prognosis after TACE than the PE cHCC-CC group, but poorer response and prognosis than the HCC-control group. Enhancement patterns at recurrence were crucially associated with tumor response and overall survival.